2013
DOI: 10.1080/13607863.2013.790930
|View full text |Cite
|
Sign up to set email alerts
|

Does self-reported sleep quality predict poor cognitive performance among elderly living in elderly homes?

Abstract: Poor quality of sleep is related to cognitive impairment among elderly living in elderly homes and this problem should be taken in consideration among this group of elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
2
24
1
Order By: Relevance
“…In examining sleep quality and cognitive deficits, Amer et al found 24% of good sleepers to have cognitive deficits compared to 52% of poor sleepers on the Mini-Mental State Examination. 4 This effect of sleep on cognition was evident even when comparing individuals with mild cognitive impairment (MCI) with sleep disorders to MCI patients without sleep disorders, whereby the latter had significantly higher scores in domains such as attention, visuo-spatial/executive function compared to the former. 27 One possible reason for the insignificant finding in this study might be due to the limited number of cognitive domains that were examined in relation to sleep problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In examining sleep quality and cognitive deficits, Amer et al found 24% of good sleepers to have cognitive deficits compared to 52% of poor sleepers on the Mini-Mental State Examination. 4 This effect of sleep on cognition was evident even when comparing individuals with mild cognitive impairment (MCI) with sleep disorders to MCI patients without sleep disorders, whereby the latter had significantly higher scores in domains such as attention, visuo-spatial/executive function compared to the former. 27 One possible reason for the insignificant finding in this study might be due to the limited number of cognitive domains that were examined in relation to sleep problems.…”
Section: Discussionmentioning
confidence: 99%
“…Although evident among young and middle‐aged adults, sleep problems are particularly common among the elderly, with a large majority reporting sleep to be shallow and fragmented . In a review by Ohayon, difficulties initiating sleep were reported in 15–45% of non‐institutionalized elderly, disrupted sleep in 20–65%, early morning awakening in 15–54%, and non‐restorative sleep in about 10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared to 7 hours of sleep duration, we observed no significant difference in subjective health perception for other sleep durations. Older adults have a higher prevalence of sleep disorders; 10,11) thus, the impact of insufficient sleep duration on subjective health perception could be greater in this population than in younger populations. In other words, if older adults perceive that they are lacking sleep, their subjective health perception is likely to be worse compared to those in younger populations.…”
Section: Discussionmentioning
confidence: 99%
“…10) These observations suggest a high prevalence of sleep disorders in older adults. 11) Thus, these individuals with a high prevalence of sleep problems may also have a high possibility of reduced subjective health perception, which may ultimately affect the actual health status.…”
mentioning
confidence: 99%